Impact of controlled foreign corporation rules on post-acquisition investment and profit shifting in targets - Dominik von Hagen; Christoph Harendt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
We investigate real investment, financial revenues and profits in formerly domestic firms once they enter a multinational entity (MNE) through an acquisition. We argue that following the acquisition, those targets are tax-optimized in a profit shifting context if they are acquired by MNEs with no controlled foreign corporation (CFC) rules in their headquarters' countries. In this case, we hypothesize that MNE-wide profit shifting opportunities decrease high-tax targets' cost of capital, which may have a positive effect on real investment of these targets. In addition, we hypothesize that financial revenues respectively profits of low-tax targets increase after the acquisition, since they may become destinations of profit shifting themselves. In line with the effects on real investment, profits of high-tax targets should decline. We find evidence for the effects on real investment. Further, these effects can no longer be observed in case of existing CFC rules in the acquirer's headquarters' country. This finding may suggest that CFC rules effectively mitigate MNE-wide profit shifting which in turn has detrimental investment effects. We also find some evidence for the expected effects for financial revenues but not for the profit measure.
urn:nbn:de:bsz:180-madoc-438162
Keywords: F23; G34; H25; H26; H32; H73; 330; International taxation; CFC rules; Profit shifting; Multinational entities; Crossborder mergers and acquisitions; Foreign direct investment